Perancangan Sistem Informasi Administrasi Kependudukan Pada Desa Seri Sembilan - Kurniawan, Veri; Amroni; Yose, Imelda (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2023)
Seri Sembilan Village is one of the government agencies in Merangin Regency which has a lot of population data, but still uses a semi-computerized system in processing the data. This has weaknesses, including a lot of data or reports that are not archived properly, searching for data takes time because you have to look for one by one and limited space to accommodate files or Kelurahan data, errors occur when inputting the applicant's personal data. To overcome these problems, a solution is needed, namely by using a computerized correspondence application based on a website. This application has many advantages, including helping the population data collection process and reducing errors in inputting personal data of letter applicants in Seri Sembilan Village, especially in the process of making Birth Certificates, Death Certificates, Certificates of Incapacity, Parents' income certificates which require high accuracy and precision. So that in a short time the making of the population data collection report mentioned above can minimize errors that may occur. The purpose of this study is to analyze the current system, in order to overcome the problems faced by the Seri Sembilan Village Office, by designing a Population Administration Information System Design in Seri Sembilan Village. The system development uses a waterfall model, the implementation of this research uses the PHP language and uses the MySQL DBMS database to produce data processing applications that are expected to facilitate data processing and report generation